The Effect of Mercury Exposure to Escherichia Coli Bacteria Resistant to Mercury and Escerichia Coli Esbl in Vitro - Retno Kusumawati, Diah (Jurnal Medis Islam Internasional, 2021)
Background: The level of pollution in Indonesia is still very high, consist of water pollution, air pollution and soil pollution. Mercury is one of the heavy metals that pollutes the waters of the sea, while Escherichia coli is exposed to mercury will try to defend itself by doing mercury detoxification so that it can live in an environment that contains mercury. Escherichia coli that tries to defend itself from mercury exposure in the environment will experience a change in its genes into mercury resistant Escherichia coli. In plasmids or transposons, it might also stimulate the formation of resistance genes for some antibiotics, include producing the ESBL enzyme, so that it can convert non ESBL Escherichia coli into ESBL Escherichia coli. Objective: This study aims to prove that the repeated exposure of mercury will change non ESBL-mercury sensitive Escherichia coli into ESBL- mercury resistant Escherichia coli. Method: This was an experimental study with 27 non-ESBL Escherichia coli isolates as identified from Phoenix. Non-ESBL Escherichia coli clinical isolates were tested by giving exposure to HgCl2 with concentrations of 0.02 ppm, 0.10 ppm, 0.20 ppm for 1-14 days until mercury resistant Escherichia coli was formed, and then ESBL screening was tested by giving Cefotaxime exposure to them. Results:  On the first day of mercury exposure, there were 9 isolates of 0.02 ppm HgCl2 resistant Escherichia coli, 9 isolates of 0.10 ppm HgCl2 resistant Escherichia coli, 9 isolates of 0.20 ppm HgCl2 resistant Escherichia coli. Furthermore, this Escherichia coli isolate was exposed to Cefotaxim as ESBL screening. The final results of post-exposure HgCl2 0.02 ppm was obtained 3 (33.3%) isolates were still sensitive to Cefotaxime and 6 (66.7%) isolates that were resistant to Cefotaxime. The final results of post-exposure HgCl2 0.10 ppm was obtained all 9 (100%) isolates that were resistant to Cefotaxime. The final results of post-exposure HgCl2 0.20 ppm obtained 2 (22.2%) isolates were still sensitive to Cefotaxime and 7 (77.8%) isolate were resistant to Cefotaxime. Conclusion: Escherichia coli in urine had the phenotive change into mercury resistant Escherichia coli. Mercury exposure of 0.02 ppm, 0.10 ppm, 0.20 ppm for 1 day in vitro on isolates of non ESBL-mercury resistant Escherichia coli caused changes in 22 isolates of Escherichia coli in urine